PENGARUH GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Prasekti, Rizky Putri; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of Good Corporate Governance, Corporate Social Responsibility, and financial performance to the firm value. The firm value is measured by using Tobinâs Q ratio. The population is the manufacturing companies which are listed in Indonesia Stock Exchange (IDX) during 2009-2013 periods. The samples are 41 manufacturing companies which have been selected by using the purposive sampling method with the criteria i.e.: first, the company which has published its annual report consecutively; second, the company which has conducted CSR disclosure during 2009-2013 periods; and finally, the company which presents its financial statement by using Rupiah currency. Based on the result of the multiple linear regressions analysis, it has been found that: first Good Corporate Governance has negative influence to the firm value; second, Corporate Social Responsibility has positive and significant influence to the firm value; third, Return on Assets has positive influence to the firm value; and finally, Return on Equity has negative influence to the firm value.Keywords: Good Corporate Governance, Corporate Social Responsibility, Financial Performance, and Firm Value